Spray-Dried Porcine Plasma Promotes the Association Between Metabolic and Immunological Processes at Transcriptional Level in Gilthead Sea Bream (Sparus aurata) Gut - Vallejos Vidal, Eva Carolina.; Reyes Cerpa, Sebastián.; Tort, Lluis; Polo, Javier; Reyes López, Felipe E.; Gisbert, Enric (Frontiers Media S.A., 2022)
The spray-dried porcine plasma (SDPP) is an abattoir by-product used in animal nutrition with beneficial effects reported in livestock and commercial aquatic species. Previous results have found that the dietary inclusion of SDPP in gilthead sea bream (Sparus aurata) increased the density of intestinal goblet cells, and it did not result in significant changes in the autochthonous microbiota. However, there is no comprehensive data on the mechanisms that could take place on the intestine of gilthead sea bream fed with an SDPP-supplemented diet. For this reason, this study aimed to unveil the biological mechanisms modulated in response to the dietary administration of SDPP in the gilthead sea bream gut. To achieve this goal, we made a microarrays-based transcriptomic approach in gut samples from gilthead sea bream fed with an SDPP-supplemented diet for 95 days. As control diet, we used a protein-rich commercial feed (51% crude protein, 17% crude fat, and 20.6 MJ/kg gross energy) which was supplemented with 3% SDPP at the expense of LT70 fishmeal. The microarray analyses showed a total of 803 (468 up- and 335 down-regulated) differential expressed genes (DEGs). The functional network analysis revealed that dietary inclusion of SDPP induced sustained changes in 120 biological processes, grouped in 12-clusters. Among them, the metabolic-related process (cellular catabolic process, organic substance catabolic process, protein metabolism process), protein transport, and leukocyte mediated immunity interacted in the leading interactome network. This evidence confirms the previous evidence of the enhancement of the mucosal health status in response to the dietary administration of SDPP and provides further understanding of the mode of action of this ingredient in aquafeeds.
Keywords: Teleost fishes; Dietary additives; Inmune response; Mucosal-Associated Lymphoid Tissue (MALT); Spray-Dried Porcine Plasma (SDPP); Aquaculture